2018
DOI: 10.15252/emmm.201809014
|View full text |Cite
|
Sign up to set email alerts
|

USP 14 inhibition corrects an in vivo model of impaired mitophagy

Abstract: Mitochondrial autophagy or mitophagy is a key process that allows selective sequestration and degradation of dysfunctional mitochondria to prevent excessive reactive oxygen species, and activation of cell death. Recent studies revealed that ubiquitin–proteasome complex activity and mitochondrial membrane rupture are key steps preceding mitophagy, in combination with the ubiquitination of specific outer mitochondrial membrane (OMM) proteins. The deubiquitinating enzyme ubiquitin‐specific peptidase 14 (USP14) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 58 publications
1
73
0
Order By: Relevance
“…Though USP14 is more pronounced for its therapeutic potential in cancer (Shinji et al, 2006;Liao et al, 2018;Han et al, 2019), its role in neurodegenerative disorders is also known (Boselli et al, 2017;Min et al, 2017;Chakraborty et al, 2018). It is well accepted that the influence of USP14 on proteasome complex activity is inversely correlated (Lee et al, 2010;Kim and Goldberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Though USP14 is more pronounced for its therapeutic potential in cancer (Shinji et al, 2006;Liao et al, 2018;Han et al, 2019), its role in neurodegenerative disorders is also known (Boselli et al, 2017;Min et al, 2017;Chakraborty et al, 2018). It is well accepted that the influence of USP14 on proteasome complex activity is inversely correlated (Lee et al, 2010;Kim and Goldberg, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Among the DUBs, USP14 is unique as it can influence autophagy (Xu et al, 2016) and UPS activity (Lee et al, 2010;Kim and Goldberg, 2017) independently, both are the prerequisites for mitophagy. Recently, it was demonstrated that USP14 inhibition enhances mitophagy and protects against the disease progression in Drosophila model (Chakraborty et al, 2018). So the current understanding depicts that higher levels of USP14 may influence UPS activity, autophagy, and in turn mitophagy levels.…”
Section: Deubiquitinases In Parkinson's Disease: a Brief Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…All cell lines were cultured in DMEM solution that contained 4.5 g/L d-glucose, 10% FBS, 2 mm l-glutamine, 100 U/mL penicillin, 100 mg/mL streptomycin, 1 mM sodium-pyruvate, and a 1% solution of nonessential amino acid. TEM samples and image acquisition was performed as reported in Chakraborty et al (2018). The width of contact sites is highlighted with white arrowhead.…”
Section: Mtdna and Mercs: A Preliminary Correlative Analysismentioning
confidence: 99%